2003
DOI: 10.1091/mbc.e02-10-0682
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dynein Light Intermediate Chain Colocalizes with the Retrograde Motor for Intraflagellar Transport at Sites of Axoneme Assembly inChlamydomonasand Mammalian Cells

Abstract: The assembly of cilia and flagella depends on bidirectional intraflagellar transport (IFT). Anterograde IFT is driven by kinesin II, whereas retrograde IFT requires cytoplasmic dynein 1b (cDHC1b). Little is known about how cDHC1b interacts with its cargoes or how it is regulated. Recent work identified a novel dynein light intermediate chain (D2LIC) that colocalized with the mammalian cDHC1b homolog DHC2 in the centrosomal region of cultured cells. To see whether the LIC might play a role in IFT, we characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(147 citation statements)
references
References 76 publications
(148 reference statements)
6
139
1
1
Order By: Relevance
“…LC8 has been assumed to be part of the retrograde IFT motor complex because the absence of LC8 in Chlamydomonas results in defects in this process (Pazour et al, 1998); however, it was not observed to copurify with the DHC1b-D1bLIC complex (Perrone et al, 2003). We found that LC8 co-purified with FAP133 in sucrose gradients (Fig.…”
Section: Fap133 Associates With Lc8mentioning
confidence: 73%
See 2 more Smart Citations
“…LC8 has been assumed to be part of the retrograde IFT motor complex because the absence of LC8 in Chlamydomonas results in defects in this process (Pazour et al, 1998); however, it was not observed to copurify with the DHC1b-D1bLIC complex (Perrone et al, 2003). We found that LC8 co-purified with FAP133 in sucrose gradients (Fig.…”
Section: Fap133 Associates With Lc8mentioning
confidence: 73%
“…basal-body localization of DHC1b (Hou et al, 2004;Perrone et al, 2003). To determine whether the protein levels and subcellular localization of FAP133 are affected by the absence of specific subunits of the retrograde IFT dynein motor, we employed three Chlamydomonas null mutant strains; dhc1b, d1blic and fla14, which lack the DHC1b, D1bLIC and LC8 genes, respectively (Hou et al, 2004;Pazour et al, 1999;Pazour et al, 1998).…”
Section: Journal Of Cell Science 120 (20)mentioning
confidence: 99%
See 1 more Smart Citation
“…The DYNC2LI1 subunit was first identified in mammals and, subsequently, in Chlamydomonas and C. elegans (Grissom et al, 2002;Hou et al, 2004;Perrone et al, 2003;. Chlamydomonas mutants that are null in the gene encoding the DYNC2LI1 homolog (D1bLIC) display a phenotype similar to that of DHC1b null mutants in that the mutant cells assemble short flagella that are filled with IFT particles (Hou et al, 2004).…”
Section: The Retrograde Ift Motormentioning
confidence: 99%
“…This process was first identified microscopically in the flagella of the single-celled green alga Chlamydomonas reinhardtii (8), and it was later shown by electron microscopy that "trains" of IFT particles move between the ciliary membrane and the underlying axonemal outer doublet microtubules (9). The driving force for this movement is provided by motor proteins that were identified as heterotrimeric kinesin II for anterograde transport (9 -11) and cytoplasmic dynein 1b for retrograde transport (12)(13)(14)(15). The IFT particles contain arrays of the so-called IFT complex that consists of two distinct subcomplexes, IFT-A and IFT-B, containing at least 6 and 14 subunits, respectively (10, 16 -22).…”
mentioning
confidence: 99%